Contextual Factors of Performance Management Exemplified by a Selection of State Sanitary Inspections - Ulrych , Wojciech (Studia Oeconomica Posnaniensia, 2016)
A State Sanitary Inspection (SSI) performs the important duties of control and supervision over the hygiene conditions in various spheres of public and private life in the country. The effectiveness of SSI execution units (i.e. local Sanitary and Epidemiological Station, SES) is determined by many contextual factors. Many of these factors are found to be the barriers and difficulties in performance management at individual, team, and organizational levels. The paper presents the results of the research in the field of these barriers. The findings indicate that the main barriers, or difficulties, in the implementation of SES statutory objectives refer to fundamental operation processes funding and administrative assistance. The situation is largely the result of the current restructuration processes. Financial problems are associated with the subsequent difficulties in maintaining the quality of services provided, as well as the uncertainty about the employees layoff s. The conclusion states that the direction of change towards bigger SSI flexibility is a good choice, although at this stage of the changes, there are still no improvements in terms of its financing.